Pengaruh Teknologi Informasi Terhadap Peningkatan Efisiensi Proses Bisnis di Sektor Perbankan - Laura Gusti Ayunda (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This research aims to analyze the influence of the application of information technology on increasing the efficiency of business processes in the banking sector. In an increasingly competitive and dynamic business environment, operational efficiency is one of the keys to success for banks. The application of information technology through various digital systems, such as Internet Banking, Mobile Banking, and cloud computing-based platforms, has been proven to speed up transactions and reduce operational costs. Apart from that, automating business processes through ERP and CRM also increases accuracy and makes data-based decision making easier. However, the implementation of this technology faces challenges, such as limited technical skills and organizational cultural resistance. However, proper use of IT can increase productivity, customer satisfaction and strengthen the bank's competitive position. This research provides insight into the importance of IT investment in supporting digital transformation and operational efficiency in the banking sector.